Labor earnings respond differently to income-tax and to payroll-tax reforms - Etienne Lehmann; François Marical; Laurence Rioux (Institute for the Study of Labor (IZA), 2011)
We estimate the responses of gross labor earnings with respect to marginal and average net-of-tax rates in France over the period 2003-2006. We exploit a series of reforms to the income-tax and the payroll-tax schedules that affect individuals who earn less than twice the minimum wage. Our estimate for the elasticity of gross labor earnings with respect to the marginal net-of-income-tax rate is around 0.2, while we find no response to the marginal net-of-payroll-tax rate. The elasticity with respect to the average net-of-tax rates is not significant for the income-tax schedule, while it is close to -1 for the payroll-tax schedule. A plausible explanation is the existence of significant labor supply responses to the income-tax schedule, combined with a short-term rigidity of the hourly taxable wage (i.e. the gross wage minus payroll taxes), casting doubts about public finance analysis that assumes perfect competition on the labor market. Finally, the effect of the net-of-income-tax rate seems to be driven by labor supply participation decisions, in particular those of females.
urn:nbn:de:101:1-201111213517
Keywords: H24; H31; J22; J38; 330; labor earnings; payroll tax; income tax; Einkommen; Einkommensteuer; Lohnsteuer; Steuerreform; Steuerwirkung; Arbeitsangebot; Schätzung; Frankreich